Early diagnosis of coeliac disease in the Preventive Youth Health Care Centres in the Netherlands: study protocol of a case finding study (GLUTENSCREEN) - Johanna Escher; Nan van Geloven; Martine Charlotte de Vries; Caroline Meijer-Boekel; M.Elske van den Akker; Leti van Bodegom; Floris van Overveld; Edmond H H.M Rings; Lucy Smit; M. Luisa Mearin (BMJ Publishing Group, 2021)
Introduction Coeliac disease (CD) occurs in 1% of the population, develops early in life and is severely underdiagnosed. Undiagnosed and untreated disease is associated with short-term and long-term complications. The current healthcare approach is unable to solve the underdiagnosis of CD and timely diagnosis and treatment is only achieved by active case finding. Aim: to perform a case finding project to detect CD children who visit the Youth Health Care Centres (YHCCs) in a well-described region in the Netherlands to evaluate whether it is feasible, cost-effective and well accepted by the population.Methods/analysis Prospective intervention cohort study. Parents of all children aged 12 months and 4 years attending the YHCCs for a regular visit are asked whether their child has one or more CD-related symptoms from a standardised list. If so, they will be invited to participate in the case finding study. After informed consent, a point of care test (POCT) to assess CD-specific antibodies against tissue transglutaminase (TG2A) is performed onsite the YHCCs. If the POCT is positive, CD is highly suspected and the child will be referred to hospital for definitive diagnosis according to the Guideline Coeliac Disease of the European Society for Pediatric Gastroenterology, Hepatology and Nutrition guideline.Main outcomes Incidence rate of new CD diagnoses in the study region in comparison to the one in the same age diagnosed by standard of care in the rest of the Netherlands.Feasibility and cost-effectiveness of active CD case finding at the YHCCs. All costs of active case finding, diagnostics and treatment of CD and the potential short-term and long-term consequences of the disease will be calculated for the setting with and without case finding.Ethical acceptability: by questionnaires on parental and healthcare professionals' satisfaction.A statistical analysis plan was prepared and is published on the GLUTENSCREEN website (Statistical-Analysis-Plan-11-5-2021_def.pdf (glutenscreen.nl) and added as annex 1).Ethics and dissemination The Medical Ethics Committee Leiden approved this study. If we prove that case finding at the YHCC is feasible, cost-effective and well accepted by the population, implementation is recommended.Trial registration number NL63291.058.17.